PENGARUH KEMUDAHAN, KEPATUHAN, DAN KEPUASAN WAJIB PAJAK TERHADAP PENGGUNAAN E-FILING DI KOTA MALANG - Ufairoh Rohmawati; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to determine the effect of convenience, compliance, taxpayer’s satisfaction on the use of E-Filing in the Malang city. The research method is associative research method with a quantitative approach. The sample in this study used random sampling with the criteria of taxpayers who already have an NPWP and those who have used E-Filing. The analysis technique used to test the hypothesis using multiple linear regression analysis. The results research are the convenience variable and the compliance variable have no effect on the use of E-Filing in Malang, while the satisfaction variable has a significant positive effect on the use of E-Filing in the Malang of city. This reseach contributes to TAM. Keywords: Ease, Compliance, Satisfaction, Use of E-Filing.